Multiple import sourcing: First evidence for German enterprises from manufacturing industries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2017)
This paper uses information on import transactions by German firms from 2009 to 2012 merged with information on characteristics of the importers taken from surveys by the Statistical Offices to document that a large share of importers engage in multiple import sourcing by importing the same good from more than one source country in a year and that a large share of total imports is due to multiple sourcing. It is shown that the probability of multiple import sourcing and the share of imports from multiple sourcing in total imports increase with firm productivity and firm size after controlling for detailed industry affiliation.
Keywords: F14; 330; Imports; Multiple import sourcing; Transaction level data; Germany